PENGARUH KETERAMPILAN MENJELASKAN DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN IPS DI SMP NEGERI 5 PEKANBARU - Rowiya, Nikmatul; Suarman, Suarman; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this study aims to describe the skills and know how the concern of parents toward learning outcomes grade VII in the IPS subjects in SMPN 5 Pekanbaru. The population in this research is the entire students in the class VII of SMPN 5 Pekanbaru of 292 totalling Soweto students. This research uses a simple random sample that the sample population members taking done at random without regard to existing in the population strata with a total of 169 students who made the sample. Data were collected using a questionnaire about the skills explain and attention parents distributed to respondents as well as asking for a list to student learning outcomes. Data analysis data analysis using linear multiple regression test with a significant level of 5%. . In descriptive, describing skills including on the category either (58.0%), attention parents included in the category of less well (49.1%), and the results of the study include enough (52.7%). Based on the research results influence skills explain and attention parents give donations influence on student learning outcomes of 45.8% with the regression equation Y = 47,427 + 0, 432XI + 0, 239X2.Key Words: Skills Explained, The Attention Of The Parents, Learning Outcomes